2022
DOI: 10.1039/d2ta06339e
|View full text |Cite
|
Sign up to set email alerts
|

Thin film nanocomposite membranes of superglassy PIM-1 and amine-functionalised 2D fillers for gas separation

Abstract: Loss of free volume over time (i.e. aging) is the main hurdle towards the commercial use of super glassy polymers for gas separation membranes. Aging takes place at a much...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 52 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…In conclusion, the long-term gas separation performance of the prepared MMMs, compared to PIM-1-based membranes, 112 This journal is © The Royal Society of Chemistry 2024 demonstrated that they maintain excellent separation efficiency over extended operational periods.…”
Section: Composite Membranes Based On Defective 2d Nanomaterialsmentioning
confidence: 84%
See 1 more Smart Citation
“…In conclusion, the long-term gas separation performance of the prepared MMMs, compared to PIM-1-based membranes, 112 This journal is © The Royal Society of Chemistry 2024 demonstrated that they maintain excellent separation efficiency over extended operational periods.…”
Section: Composite Membranes Based On Defective 2d Nanomaterialsmentioning
confidence: 84%
“…8(a). 112 Scanning Electron Microscopy (SEM) images indicated that the original PIM-1 thin-membrane composite (TFC) membranes possessed a smooth, dense surface and cross-section. With the addition of amine-functionalized rHGO to the PIM-1 matrix, forming TFN-rHGO-TAPA-TFC membranes, the resulting membranes displayed impeccable surface integrity without any defects and exhibited a uniform dispersion of fillers within the polymer matrix, absent of visible agglomerates, as depicted in Fig.…”
Section: Composite Membranes Based On Defective 2d Nanomaterialsmentioning
confidence: 99%
“…The polymer synthesis procedures employed to obtain PIM-1 polymers, B2, B17 and B11, are outlined in Section S2. Modifications which produced branched PIM-1 samples have been previously reported in the literature [29][30][31][32], with the underpinning theory to produce highly branched PIM-1, such as B17 and B11, outlined in a more recent publication [33]. The polymers were purified and then characterised as described in Section S3.…”
Section: Pim-1 Synthesismentioning
confidence: 99%
“…These results show that the different PIM-1 structures have a significant impact on the permeation properties of the F-gas molecule. Both self-standing films and thin film composite gas separation membranes from more highly branched PIM-1 polymers tend to exhibit lower initial permeabilities than disubstituted samples, but then age at a much slower rate over time [29,30,32,37].…”
Section: F-gas Permeability and Ideal Selectivitymentioning
confidence: 99%
“…Many porous solids have been tested as fillers, ranging from inorganic to inorganic–organic hybrids to completely organic frameworks. Organic materials can be easy to obtain with low costs of production. One example is represented by hyper-cross-linked polymers (HCPs), , already used within mixed matrix membranes (MMMs). ,, …”
Section: Introductionmentioning
confidence: 99%